2016
DOI: 10.3164/jcbn.16-19
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of reactive oxygen species derived from mitochondria in neuronal injury elicited by methylmercury

Abstract: Methylmercury induces oxidative stress and subsequent neuronal injury. However, the mechanism by which methylmercury elicits reactive oxygen species (ROS) production remains under debate. In this study, we investigated the involvement of mitochondrial ROS in methylmercury-induced neuronal cell injury using human neuroblastoma SH-SY5Y-derived ρ0 cells, which have a deletion of mitochondrial DNA and thus decreased respiratory activity. SH-SY5Y cells were cultured for 60 days in the presence of ethidium bromide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…Moreover, we also found that MeHg inhibited the expression of HIF-1a in the SD rat brain, which better revealed the relationship between MeHg and the HIF-1a signaling pathway found in the in vitro and in vivo experiments. MeHg is an established neurotoxicant (Aschner and Syversen 2005;Clarkson and Magos 2006;Culbreth and Aschner, 2016;Farina et al 2011aFarina et al , 2011b, whose mechanism(s) of toxicity have yet to be fully understood; however, oxidative stress seems to play a role (Aschner et al 2007;Santos et al 2018;Ishihara et al 2016). Oxidative stress is one of the known mechanisms for the induction of HIF-1a.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we also found that MeHg inhibited the expression of HIF-1a in the SD rat brain, which better revealed the relationship between MeHg and the HIF-1a signaling pathway found in the in vitro and in vivo experiments. MeHg is an established neurotoxicant (Aschner and Syversen 2005;Clarkson and Magos 2006;Culbreth and Aschner, 2016;Farina et al 2011aFarina et al , 2011b, whose mechanism(s) of toxicity have yet to be fully understood; however, oxidative stress seems to play a role (Aschner et al 2007;Santos et al 2018;Ishihara et al 2016). Oxidative stress is one of the known mechanisms for the induction of HIF-1a.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl mercury. This neurotoxic compound was used as a reference compound since several results have already been published applying mono-culture approach, 14,[32][33][34][35] and few with co-culture approach. 6,7 Methyl mercury concentrations of 1 and 2.5 mM were applied based on its cytotoxicity to cerebellar granular cells after 1-hour exposure, causing a 50% reduction in cell viability, respectively, as evaluated by MTT test.…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…32 In SH-SY5Y neurons, the lethal concentration 50 (LC 50 ) of MeHg (evaluated by MTT) after 24-hour exposure was reported to be about 7 mM, 33 and in a more recent investigation, when SH-SY5Y cells were treated with MeHg for 24 hours, approximately 40% of cells died following 1 mM MeHg treatment and almost all cells died after 10 mM MeHg. 35 Methyl mercury stock solution (2.5 mM) was prepared by dissolving the powder in dimethyl sulfoxide (DMSO). From the stock solution, appropriate work dilutions were made in DMEM growth medium containing 10% FBS.…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…One of the main mechanisms of MeHg-induced neurotoxicity is oxidative stress. We have reported that mitochondrial ROS injures neurons under MeHg exposure 6 . Because treatment with an antioxidant, namely, vitamin E, at the same time as MeHg administration suppressed the delay of latency and increases in the threshold at the IC (data not shown), oxidative stress generated by MeHg exposure could induce IC dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…MeHg also inhibits the activity of glutathione reductase to attenuate the regeneration of reduced glutathione 5 . We previously reported that ROS generated inside cells by MeHg exposure are amplified in mitochondria to induce further neuronal damage 6 , suggesting that mitochondria play an important role in MeHg-induced neuronal injury. Some reports have suggested possible mechanisms of MeHg-induced neuronal damage other than oxidative stress, including disruption of microtubules 7 , decreases in intracellular ATP 8 and apoptosis 6 .…”
Section: Introductionmentioning
confidence: 99%